Analysis of the Effectiveness of using the Learning Approach in the Implementation of Online Learning in Elementary Education - Ni Made Indrayani; La Ode Safiun Arihi; Ali Hadara; Hasniah Hasniah (Universitas Negeri Malang, 2023)
This study aims to determine the dominance of the learning model approach in online learning.Many learning models make it important to study, especially regarding the learning modelapproach used in online learning (e-learning, blended learning). This study uses a descriptivequalitative study obtained from a journal review. Data sources come from international journalsreviewed starting in 2020–2022, where online learning occurred during the pandemic. The datawere then analyzed using QDA (qualitative data analysis) to obtain average data and percentagesfor each learning model. The learning model studied is limited to problem-based, project-based,and cooperative learning. The analysis showed that online learning had the highest percentageduring the pandemic, namely problem-based learning at 42.6%, project-based learning at 37.6%,and cooperative learning at 19.8%. This shows that the teacher uses a problem-based learningmodel approach when presenting material or concepts during online learning